PROPUESTA DE DISEÑO DE LA RUTA AGROTURÍSTICA DEL ARROZ EN LA PARROQUIA ELOY ALFARO DEL CANTÓN MACARÁ, PROVINCIA DE LOJA - Álvarez Sarango, Bolívar Javier (2019)
The tourism sector in Ecuador is a very important component for income generation, employment and production; It has allowed the growth of food, lodging, transportation, intermediation sectors, among others. Reason why it is necessary to plan its development and conservation of the resources used in it, through the necessary adoption of a long-term vision of the activity. The UNWTO consultant, Lic. Federico Wyss, who delivered a report called “Bases for the development of rural tourism in Ecuador”, together with PLANDETUR propose the potential use of farms, farms and plantations as a tourist resource, very similar in concept to the theme parks, for their agricultural and cultural aspect, educational value, recreational potential and scientific contributions. In the South of Ecuador in the Province of Loja we find the Macará Canton exuberant in natural and cultural resources that are used for agriculture and livestock, the Eloy Alfaro Parish is an example of agricultural production, especially rice and its commercialization. In view of the fact that the Eloy Alfaro parish has an agricultural potential for rice fields and agricultural and livestock production, it was important to develop this research work based on the Agrotourism Routes, for this purpose a general objective was proposed: “Design Proposal of the Rice Agrotourism Route for the Eloy Alfaro Cantón Macará Parish, Loja Province”. For the fulfillment of the general objective, three specific objectives were considered: the first objective: To carry out the Tourist Diagnosis of the Macará Canton, Loja Province, for this purpose, the Analytical Method was used to perform an analysis of the tourist attractions of the Eloy Alfaro parish ; the Inductive Method, which was used for the analysis of the particularities of the Macará canton in economic and socio-cultural aspects; thus also the techniques of direct observation and interview were applied; In addition, the diagnostic matrix of communities of Carla Ricaurte Quijano, Tourist Inventory Sheets (MINTUR) and hierarchy of tourist attractions. The support of the Territorial Planning Plan served as a complement to information gathering; geography, tourism, economics, politics and social; Finally, the SWOT matrix was carried out to determine 6 the current situation of the canton. In the second objective: To elaborate the Proposal for the Design of the Agritourism Route of the Eloy Alfaro Parish, of the Macará Canton, for the same the Synthetic Method was used that allowed to determine which communities were integrated into the tourist activity, taking into account the potential that they also have the use of the Global Positioning System (GPS), to carry out the geographical coordinates of the tourist attractions, as well as times and distances between them; camera, and the matrix to validate tourist routes, designed by Gustavo Xavier Álvaro Silva; In addition, pictograms of tourist attractions, activities and services were used for the design and preparation of the route map, additionally an identifying mark was created using the main elements that stand out within it. The third objective: Propose Strategies for the Development of the Agrotourism Product Posed; This stage has an impact on formulating strategies that will allow Macará to work for tourism, manage tourism planning in the GAD, trainings and conduct the first participatory workshop in the parish. The result determined that the “Macará Border Agrotourism Route” will contribute to the promotion of Agricultural and agricultural activity as a new tourist alternative for the canton. With the academic contribution of this research work, we intend to change the way we see agricultural work, from a different point of view. Another important feature is the search to contribute to the rescue and revaluation of traditional agricultural knowledge in the farms of the peasant families belonging to the Canton, knowing that agrotourism is an activity of transformation of the productive matrix of the area. It tries to take a step forward in the development of tourism. Finally, the conclusions and recommendations of the thesis work that were mostly addressed to the Decentralized Autonomous Government of the Macará Canton and to the producers who own the farms and estates of the Eloy Alfaro Parish considered in the Route were raised; where the great agricultural production of rice and livestock was established that can be used for the creation of new tourist alternatives.